OLEORESIN FROM GINGER USING EXTRACTION PROCESS WITH ETHANOL SOLVENT - Dwi Daryono, Elvianto (Jurnal Teknik Kimia, 2011)
Use of ginger was grow commercially in processing that use appropriate technology. Refining of oiland ginger oleoresin from ginger rhizome growing to be a raw material in pharmaceutical companiesmanufacture drugs. Components of chemical compounds contained in ginger consists of oil evaporated,oil does not evaporate and starch. This research aims is to extraction of ginger oleoresin. Variables thatperformed in this study include the extraction temperature (30, 40, 50 and 60 ° C) and extraction time (1,1.5, 2, 2.5 and 3 hours). While the operating conditions involved the comparison of materials andsolvents of etanol 70%, materials size measure ± 40 mesh, ginger type of emprit and speed turn around60 rpm. Ginger powder counted 300 gram and solvent 1500 ml entered into ekstraktor with time andtemperature of extraction according to variable. After finishing result of extraction entered into rotaryvacuum evaporator to be dissociated between oleoresin and solvent. Analysis batchwise to specific gravity,refractive index, rendemen and % gingerol. The best condition got by at oleoresin extraction of gingerwith temperature of extraction 40oC and time of extraction 3 hour, where got specific gravity 0,9012 gr /cm3, refractive index 1,4769, rendemen 9,98% and % gingerol 33,23%.Keywords : extraction, ginger, oleoresin